Eliciting Salient Factors in Online Shopping Behavior Research - Laila Refiana Said (Universitas Sebelas Maret, 2018)
This paper argues the importance of an exploratory study prior to hypotheses testing in any causal-effect or explanatory predictive behavioral research. It proposes a stage of eliciting salient factors using a framework from theory of planned behavior. The paper opted for an exploratory study by firstly examining 12 academic research of online shopping behavior in Indonesia. Secondly, using the open-ended questions given to 30 respondents, the paper explored reasons respondents shop or not shop online. Those immediate responses were documented and termed as salient factors. Thirdly, the salient factors were then combined with foregone factors based on literature reviews. The final set of factors was chosen as predictive variables in order to provide more accurate potential antecedents for predicting and explaining online shopping behavior. The paper provides sound and practical guidance in eliciting salient factors and formulating a final set of factors in causal-effect/explanatory predictive behavioral research on online shopping behavior. It suggests that academic research should place importance on the stage of eliciting salient factors. Foregone factors are used to strengthen the choice of predictive variables. Both salient and foregone factors are necessary for the final set of factors in such online shopping behavior studies. The paper includes implications for the online vendors and government agencies to promote e-commerce. This paper fulfils a need to conduct exploratory study on online shopping behavior to understand such phenomenon of high internet penetration yet low rate of online buying behavior by focusing on salient factors of the studies.